Violencia vicaria un análisis del Derecho Internacional de los Derechos Humanos - Patiño Izquierdo, Claudia Sevigne (2023)
This paper critically examined the need to implement vicarious violence in the Ecuadorian legal system. To address this issue, a qualitative approach was used involving inductive-deductive, analytical-synthetic, dogmatic and comparative methods, together with bibliographic review techniques and case files. Theoretically, the importance of incorporating vicarious violence was justified as a way of protecting the rights of indirect victims of violence and establishing a clear line of legal responsibility. In addition, the collision between existing legal provisions and the need to adequately address vicarious violence in the Ecuadorian legal context was analyzed. In conclusion, the need for legislative reform that harmonizes the rights of indirect victims with the principle of justice and protection in the legal sphere was argued